1977
DOI: 10.1159/000117597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rubidium, Lithium and Cesium on Brain ATPase and Protein Kinases

Abstract: The authors studied the effect of rubidium, lithium and cesium on the ATPase system and c-AMP protein kinase in brain. They demonstrated that rubidium could replace potassium in the Na+K+-ATPase system, whereas lithium and cesium had no effect on this enzyme activity in the absence of potassium. K+-dependent ATPase was activated by even low rubidium concentrations; lithium and cesium inhibited it. None of three (rubidium, lithium and cesium) affected c-AMP protein kinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It has also been found that rubidium and manganese, in addition to zinc, are preferentially taken up by tumors in the brain . It could replace potassium in the Na + K‐ATPase (sodium‐potassium pump) system . Rubidium chloride might have application in future psychochemical research and therapy of the affective disorders such as depressions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been found that rubidium and manganese, in addition to zinc, are preferentially taken up by tumors in the brain . It could replace potassium in the Na + K‐ATPase (sodium‐potassium pump) system . Rubidium chloride might have application in future psychochemical research and therapy of the affective disorders such as depressions .…”
Section: Resultsmentioning
confidence: 99%
“…[23] It could replace potassium in the Na + K-ATPase (sodiumpotassium pump) system. [24] Rubidium chloride might have application in future psychochemical research and therapy of the affective disorders such as depressions. [25] Results revealed that the amount of Rb in the fresh and boiled shoots was the same (20 mg/100 g, dry weight) but increased by 10% after fermentation.…”
Section: Dendrocalamus Hamiltoniimentioning
confidence: 99%